Physical, Mechanical, and Thermal Properties and Characterization of Natural Fiber Composites Reinforced Poly(Lactic Acid): Miswak (Salvadora Persica L.) Fibers - A. F. Nur Diyana; A. Khalina; M. S. Sapuan; C. H. Lee; H. A. Aisyah; M. N. Nurazzi; R. S. Ayu (International Journal of Polymer Science)
7000 years ago, miswak fiber (MF) was used as a toothbrush for oral care. However, since the emergence of plastic materials, it monopolized the oral care industry. The increment of plastic products also promotes accumulation of plastic wastes after its disposal. Thus, many researchers have turn to biodegradable products to reduce this problem. The aim of this study is to investigate the chemical, physical, and mechanical properties of MF as reinforcement in composites that are suitable to replace the toothbrush materials. The MF was reinforced in PLA composite with different weight percentage (0%, 10%, 20%, and 30%) and undergoes several types of testing. The chemical results show that there were high presence of cellulose in the fiber which could act as medium to transfer stress load equally from fiber to matrix. However, the results show low cellulosic contents in MF that affects the poor interfacial bonding between fiber and matrix. Physical properties shows a positive indication to be used as a toothbrush handle. As the fiber content increases, the density also increased. SEM micrographic illustrated the presence of voids as the cause for reduction in mechanical properties of composites. The mechanical results show the proposed material is comparable to the materials used in commercial applications. As for the thermal result, the TGA test melting point of the proposed composite material was comparable to the pure PLA, which means the proposed material can use similar processing temperature as PLA. DSC shows that Tg of PLA/MF composite is found to be similar to Tg in loss modulus of composites. DMA finding found that PLA/MF30 have the highest storage modulus 2062 MPa and the lowest tan δ 0.6 among PLA/MF composites. This concludes that there is a possibility of using these materials as an alternative in composites and increase the fiber strength by using pretreatments and/or compatibilizer.